Climate Change and Young People in Uganda: A Literature Review - Mugeere, Anthony; Barford, Anna; Magimbi, Paul (SAGE Publications, 2021)
The disruptions of anthropogenic climate change are increasingly severe. People living in sub-Saharan Africa are especially exposed to these risks, and amongst them young people. It is well established that climate disruptions have the potential to halt education, displace populations, and wreck infrastructure. This rigorous literature review focuses on climate change in the landlocked East African country of Uganda, demographically the world’s third youngest country, where young people struggle to get by due to insufficient work opportunities. Extended to other countries in the Eastern and Central African region, the review considers what is known about the intersection of youth livelihoods and climate change; young people’s susceptibility to climate disruption due to limited resources and livelihood options; and the constraints around their responses. The review findings suggest the need for substantial youth informed interventions to bolster young people’s economic resilience and adaptive capacity given the worsening climate change and prolonged population growth.
Keywords: youth, livelihoods, work, policy, Africa, environment, activism